A Novel Machine Learning Technique towards Predicting the Sale of Washing Machines in a Small Organization - Kango Gopal, Madhwaraj; Bellie, Viswanath; Venugopal, Govindaraj (International Journal of Psychosocial Rehabilitation, 2020)
Machine learning has today become an important technical paradigm that is being used across all engineering disciplines to predict or convey some important information to the stakeholders involved in it. Several datasets gathered from several applications can be analyzed to arrive at conclusions. Earlier, machine learning was used only for large datasets due to the sample size, but nowadays, machine learning algorithms are used even for small datasets. In this research work, we have taken a small dataset to analyze the sale of washing machines in a small organization using machine learning techniques.